Grenzfall Krieg: Zur Darstellung der neuen Kriege nach 9/11 in der deutschsprachigen Gegenwartsliteratur - Willeke, Stephanie (transcript, 2018)
Fiend or friend? An examination of participants in war and border constructions within the context of contemporary wars depicted in German-language literature.